Regulation of Expression of the 2-Deoxy-d-Ribose Utilization Regulon, deoQKPX, from Salmonella enterica Serovar Typhimurium - Christensen, Mette (American Society for Microbiology, 2003)
Salmonella enterica, in contrast to Escherichia coli K12, can use 2-deoxy-d-ribose as the sole carbon source. The genetic determinants for this capacity in S. enterica serovar Typhimurium include four genes, of which three, deoK, deoP, and deoX, constitute an operon. The fourth, deoQ, is transcribed in the opposite direction. The deoK gene encodes deoxyribokinase. In silico analyses indicated that deoP encodes a permease and deoQ encodes a regulatory protein of the deoR family. The deoX gene product showed no match to known proteins in the databases. Deletion analyses showed that both a functional deoP gene and a functional deoX gene were required for optimal utilization of deoxyribose. Using gene fusion technology, we observed that deoQ and the deoKPX operon were transcribed from divergent promoters located in the 324-bp intercistronic region between deoQ and deoK. The deoKPX promoter was 10-fold stronger than the deoQ promoter, and expression was negatively regulated by DeoQ as well as by DeoR, the repressor of the deoxynucleoside catabolism operon. Transcription of deoKPX but not of deoQ was regulated by catabolite repression. Primer extension analysis identified the transcriptional start points of both promoters and showed that induction by deoxyribose occurred at the level of transcription initiation. Gel retardation experiments with purified DeoQ illustrated that it binds independently to tandem operator sites within the deoQ and deoK promoter regions with K(d) values of 54 and 2.4 nM, respectively.